Penggunaan Batas Wajar Aplikasi Shareit Dalam Fitur Transfer File dan File Share Zone Oleh Mahasiswa Uin Syarif Hidayatullah Jakarta - Fauzi Wibowo; Nahrowi Nahrowi (JOURNAL of LEGAL RESEARCH, 2019)
AbstractSHAREit is an application used to send various files such as videos, photos, songs, recordings, applications, memos and so on between one device and another. This application is widely used by the public, because sharing and sending files does not require a long time and is free of charge. But many people such as students do not know that using the SHAREit application allows users to commit copyright infringement. However, in copyright regulations there is also a fair use. This research uses empirical normative research methods. Students who use SHAREit generally admit to using SHAREit for economic reasons, are easy to use, and students are not aware of any applicable legal provisions. The conclusion in this study is the use of the SHAREit application's reasonable limit is allowed on the basis that the use is not for commercial use and does not harm the copyright owner.Keywords: Fair Use, SHAREit, Copyright